Financial Statement Analysis in Assessing the Financial Health of PT Pelabuhan Indonesia (Persero) - Nurlina; Wahyuni; Basri Basir (IECON, 2024)
This research aims to determine and analyze the level of financial health of the company PT. Pelindo (Persero) in accordance with the KEP-100/MBU/2002 assessment for the 2020-2023 period. Financial health criteria refer to KEP-100/MBU/2002, including return on equity (RoE), return on investment (RoI), cash ratio, current ratio, inventory turnover, collection periods, total asset turnover, and total own capital to assets . This research is quantitative causal research. Data analysis tools use financial ratios, including: Return on equity (ROE), Return on investment (ROI), Cash ratio,  Current ratio or current liabilities, Collection periods (CP), Inventory turnover, Total asset turnover or total asset turn over (TATO), Ratio of own capital to total assets. The results of this study show annual improvements in the company's financial health. In 2020 and 2021, PT Pelindo (Persero) was classified as "unhealthy" with a BBB rating and a score of 28. In 2022, the company moved up to the "healthy" category with an A rating and a score of 35, this status will be maintained in 2023 with a rating of A and a score of 33.5. This research shows an improvement in the financial health of PT Pelabuhan Indonesia (Persero), which can support strategic decision making and increase trust  investors in the future.